Seasonal Variability Affecting Lactation Traits in Bunaji and Friesian Crosses - Ma’aruf, B.S.; Kabir, M.; Yahaya, H.K.; Zahraddeen, D. (Nigerian Journal of Animal Science, 2026)
This study was conducted to evaluate the effect season on lactation traits of Bunaji and Friesian crosses at National Animal Production Research Institute. Lactation records of 178 cows from January 2015 to August 2021 were analysed for Lactation length (LL), Total Milk Yield (TMY) Average daily milk yield (ADMY), Milk yield at early lactation (MYEL), Milk yield at mid lactation (MYML), Milk yield at late lactation (MYLL), Persistency (PER) and peak milk yield (PMY), the seasons were divided into early rain (ER) late rain (LR) early dry (ED) and late dry (LD. The data collected was subjected to normality test and was found to be skewed, it was transformed using log10 and analysed using descriptive statistics and analysis of variance using statistical analysis systems (SAS) software. Significant (p<0.05) effect of season was observed in most of the parameters across all the seasons where ED season had better overall LL, TMY, ADMY, MYEL, MYLL PER and PMY (2.42 days, 3.16 L, 0.76 L, 2.78 L, 2.70 L, 2.58 L, 1.52 days, and 0.88 L/day, respectively) than LR ED and LD season, PER in Bunaji and MYML, MYLL PER and PMY in 50% FxB are not significantly different (p>0.05). It is concluded that, early dry season exhibited better lactation traits compared to other seasons. Dairy farmers should consider the seasonal variations in lactation traits when managing their herds to optimize milk production and further research could focus on understanding the underlying mechanisms of how seasons impact lactation traits and explore potential strategies to mitigate any negative effects.